2015
DOI: 10.1242/jeb.114066
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned frequency-dependent hearing sensitivity reduction in the bottlenose dolphin (Tursiops truncatus)

Abstract: The frequency specificity of conditioned dampening of hearing, when a loud sound is preceded by a warning sound, was investigated in a bottlenose dolphin. The loud sounds were 5 s tones of 16, 22.5 or 32 kHz, sound pressure level of 165 dB root mean square (RMS) re. 1 µPa. Hearing sensitivity was tested at the same three frequencies. Hearing sensitivity was measured using pip-train test stimuli and auditory evoked potential recording. The test sound stimuli served also as warning sounds. The durations of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The quickness of this change may be explained by the fact that this animal was not naive to the hearing dampening experimental protocol and conditioning for hearing change occurs very rapidly. This dolphin had previously been exposed to warnings and loud sounds (Nachtigall and Supin, 2015) and had previously shown learned hearing sensation changes. Other work with a totally naive beluga whale (Nachtigall et al, 2016) demonstrated that the conditioning process for hearing change occurs very rapidlywithin a 36 trial session.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The quickness of this change may be explained by the fact that this animal was not naive to the hearing dampening experimental protocol and conditioning for hearing change occurs very rapidly. This dolphin had previously been exposed to warnings and loud sounds (Nachtigall and Supin, 2015) and had previously shown learned hearing sensation changes. Other work with a totally naive beluga whale (Nachtigall et al, 2016) demonstrated that the conditioning process for hearing change occurs very rapidlywithin a 36 trial session.…”
Section: Discussionmentioning
confidence: 99%
“…1 µPa, which was higher than typical of bottlenose dolphins recently wild-caught and higher than in-captivity bottlenose dolphins and other odontocete species (Au and Hastings, 2008), which were generally between 50 and 70 dB. However, her hearing was considered as still suitable for this investigation of basic hearing change processes (Nachtigall and Supin, 2015). The subject was housed in a floating pen complex off of Coconut Island in Kaneohe Bay.…”
Section: Materials and Methods Experimental Facilities And Subjectmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to what extent middle ear mechanisms such as the stapedial reflex in the case of bats, contribute to the development in hearing sensitivity following a loud emitted broadband click remains an open question (Nachtigall and Supin, 2015). Since forward masking is only acting on the auditory neurons rendered refractory by the previous stimulus, it is a highly frequency-specific phenomenon related to the width of the auditory filters and the spectra of the sound stimuli used (Popov et al 2001).…”
Section: Introductionmentioning
confidence: 99%